Management of Philadelphia chromosome-positive B-cell acute lymphoblastic leukemia in a Jehovah’s Witness using chemotherapy free regimen: A case report and review of literature - Muhammad Hassan Raza; Eiraj Khan; Alexis M Desjarlais; Salman Fazal (Leukemia Research Reports)
Introduction and Importance: Treatment of Philadelphia chromosome-positive acute lymphoblastic leukemia (pH-positive ALL) in Jehovah’s Witness (JW) using chemotherapy agents, opens an ethically and morally challenging paradigm instead of their religious practices. Case Presentation: We present a case of pH-positive B cell ALL in a Jehovah's Witness patient who refused the transfusion of blood as a part of their treatment regimen. We intended to treat this patient using a new “chemotherapy-free” approach and achieved Minimal Residual Disease (MRD) negative state with durable outcomes for the next three years. Clinical Discussion: With “chemotherapy-free” regimen, we achieved complete molecular remission without any significant side effects in our patient. Conclusion: Chemo-free approach is a promising opportunity to treat Jehovah’s witnesses with pH-positive B cell ALL as the haemoglobin and platelets remained above transfusion thresholds. However, further research is required to fully understand and implement this approach. Future clinical trials should consider including this unique patient population to better understand their needs and improve outcomes.